Pengaruh Terapi Birth Ball terhadap Kemajuan Persalinan Kala I di Klinik Putri May Sarah - Sasmitha Sasmitha; Kamelia Sinaga; Imran Saputra Surbakti; Asnita Sinaga; Rati Aksari (PPNI UNIMMAN, 2025)
Birth balls can assist mothers during the first stage of labor by promoting labor progress. Their benefits include increasing blood flow to the uterus, placenta, and baby, widening the pelvic outlet, reducing knee and ankle discomfort, providing counter-pressure on the perineum and thighs, and utilizing gravity to aid fetal descent. This process facilitates cervical dilation and shortens labor duration. This study examines the effect of birth ball therapy on first-stage labor progress in women giving birth at the Putri May Sarah Clinic, Percut Sei Tuan District, Deli Serdang Regency, in 2024. A quasi-experimental method with a two-group design was used, involving 20 participants. Data analysis was conducted using the Mann-Whitney test. Results showed a significant difference between the intervention and control groups, with a sig value of 0.029 (<0.05) and a z-table value of 2.189. These findings indicate that birth ball therapy positively influences first-stage labor progress. Women who used birth balls experienced faster cervical dilation and fetal descent compared to those who did not. This study highlights the benefits of birth ball therapy as a non-invasive method to improve labor outcomes. The Putri May Sarah Clinic is encouraged to promote birth ball use as a supportive measure for laboring mothers. By implementing birth ball therapy, the clinic can enhance maternal comfort and facilitate a smoother, shorter first stage of labor.